The effect of nonlinear pedagogy on the acquisition of game skills in a territorial game - Chow, Jia Yi; Meerhoff, Laurentius A.; Choo, Corliss Zhi Yi; Button, Chris; Tan, Benjamin Su-Jim (Frontiers in Psychology, 2023)
Nonlinear Pedagogy (NP), underpinned by Ecological Dynamics, provides a suitable pedagogical approach for practitioners (e.g., Physical Educators, coaches) to encourage exploratory learning that is learner-centred even in Traditional Sporting Games (TSG) that could be represented by invasion or territorial-like games. NP involves the manipulation of constraints which form boundaries for interacting components to self-organise, facilitating the emergence of goal-directed behaviours. Key pedagogical principles relating to representativeness, manipulation of constraints, awareness of focus of attention instructions, task simplification and the functional role of noise can encourage exploratory learning that helps develop 21st century competencies. This is in contrast to a Linear Pedagogy (LP) approach that is more teacher-centred and focuses on repetition in practices to promote movement form consistency in enhancing the acquisition of movement skills. Little is known about the effectivity of NP in the learning and transfer of invasion games. The aims of this study were to: a) determine the impact of NP on the teaching and learning of an invasion game in the Physical Education (PE) context; b) examine the transferability of game skills to other games in the same game category (i.e., floorball as a territorial game in this study). 224 (between 12 to 13 years old) students underwent a ten-week intervention programme to learn to play an invasion game (football) with either a NP or LP approach (i.e., repetitive and prescriptive drills). Performance outcome data were measured during Pre, Post, Retention, Transfer test 1 (larger playing area) and Transfer test 2 (floorball). Significant improvements in several performance outcome and game play measures in football was observed for the NP condition. Fewer improvements in the same measures were found for the LP condition. Evidence for transfer of learning for NP was not as strong as anticipated although there was still some potential for encouraging transfer of learning. The key findings from this study further challenge the “one-size fits all” philosophy in the teaching of PE. Both LP and NP approaches would have a role to play in supporting teaching and learning which could be context dependent.